EDUKASI PENCEGAHAN PMK DI KELOMPOK TERNAK SUMBER REJEKI KABUPATEN SELUMA-BENGKULU - Dwatmadji Dwatmadji; Tatik Suteky; Edi Soetrisno (Jurnal Media Pengabdian Kepada Masyarakat, 2023)
Community service activities are carried out at the Sumber Rejeki Livestock Farmer Group -Sukaraja District, Seluma Regency. The activities were followed not only by the Sumber Rejeki livestock farming group but also other groups. In general, farmers already know about FMD (47.5%) some things that farmers are still very new to is that FMD can be transmitted through human traffic. The post test results showed a significant percentage increase of 85% on average. Keywords: FMD, herb, control